Getting the Picture: Defining Race-Based Stereotypes in Politics - Bouchard, Joanie (Frontiers in Political Science, 2022)
This article considers electoral inter-group dynamics in Quebec, Canada, by focusing on what White voters expect from political candidates of color. While significant work has been done on the use of political heuristics such as race or gender-based framing by the media, we do not know as much about the way voters interpret and use these stereotypes in a political context. In this article, we consider voters' interpretation of race-based cues using qualitative evidence gathered in six focus groups. First, we explore the content of stereotypes typically associated with politicians of color in the province. Second, this article provides an assessment of some of the ways in which race-based stereotypes are used to understand politics and evaluate politicians of color. We find that race-based stereotypes contribute to defining expectations regarding politicians' behavior. While voters may consciously choose to favor politicians of color, the perception of social distance between a marginalized candidate and them can also lead to negative cross-ethnic attitudes.